Synchronous Surgical Treatment of Lower Eyelid Involutional Entropion and Ptosis - D. Vasakos; E. Nakos; C. Sioulis (Case Reports in Ophthalmological Medicine)
Background. Involutional entropion and upper eyelid ptosis are common eyelid diseases in the elderly population. They represent a frequent cause of discomfort and often result in significant visual and functional impairment. The surgical management of these disorders includes various treatment options and techniques and is usually carried out in multiple time sessions. Case Report. We report the case of a 72 year old female patient, suffering from right eye involutional lower eyelid entropion and ptosis, who was treated synchronously for both conditions, by applying the lateral tarsal strip procedure and the levator resection technique. Conclusion. The synchronous treatment of involutional entropion and ptosis is an alternative treatment strategy, which could potentially improve surgical outcome, while reducing postoperative recovery time and treatment costs.